The Application of Nanoparticles Targeting Cancer-Associated Fibroblasts - Huang Q; Ge Y; He Y; Wu J; Tong Y; Shang H; Liu X; Ba X; Xia D; Peng E; Chen Z; Tang K (International Journal of Nanomedicine, 2024)
Qiu Huang,* Yue Ge,* Yu He, Jian Wu, Yonghua Tong, Haojie Shang, Xiao Liu, Xiaozhuo Ba, Ding Xia, Ejun Peng, Zhiqiang Chen, Kun Tang Department of Urology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, 430030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiqiang Chen; Kun Tang, Email zhqchen8366@163.com; tangsk1990@163.comAbstract: Cancer-associated fibroblasts (CAF) are the most abundant stromal cells in the tumor microenvironment (TME), especially in solid tumors. It has been confirmed that it can not only interact with tumor cells to promote cancer progression and metastasis, but also affect the infiltration and function of immune cells to induce chemotherapy and immunotherapy resistance. So, targeting CAF has been considered an important method in cancer treatment. The rapid development of nanotechnology provides a good perspective to improve the efficiency of targeting CAF. At present, more and more researches have focused on the application of nanoparticles (NPs) in targeting CAF. These studies explored the effects of different types of NPs on CAF and the multifunctional nanomedicines that can eliminate CAF are able to enhance the EPR effect which facilitate the anti-tumor effect of themselves. There also exist amounts of studies focusing on using NPs to inhibit the activation and function of CAF to improve the therapeutic efficacy. The application of NPs targeting CAF needs to be based on an understanding of CAF biology. Therefore, in this review, we first summarized the latest progress of CAF biology, then discussed the types of CAF-targeting NPs and the main strategies in the current. The aim is to elucidate the application of NPs in targeting CAF and provide new insights for engineering nanomedicine to enhance immune response in cancer treatment.Keywords: nanoparticles, cancer therapy, cancer-associated fibroblasts, drug delivery, cancer, nanomedicine